Optimizing pre- and post-crosslinking methods for alginate using the Triaxial tool print head with microfluidic chips or mist sprayer - Peltonen, Niko (My University, 2023)
Generally, 3D bioprinting is used as a layer-by-layer method to create tissue-like structures. Alginate is a widely used bio-ink in the biomedical field, including tissue engineering and drug delivery due to its biocompatibility, biodegradability, and non-toxicity. One of the advantages of using alginate is the possibility of crosslinking by calcium chloride (CaCl2). The main idea of crosslinking is to solidify the bio-ink into a stable structure. The project was done in a Turku-based bioprinting company called Brinter Oy. The primary aim of this master’s thesis was to design and test resin-based microfluidics to develop the mixing of alginate using Brinter’s Triaxial tool print head. Additionally, different pre- and post-crosslinking methods of alginate, such as spraying using CaCl2, were compared and analyzed. The preparation of microfluidics consisted of designing, printing, curing, and optimizing the model of the different fluidic chips. Resin-based microfluidics, which combined isopropyl alcohol (IPA) washing and UV curing, enabled high-resolution printing. Alginate bio-inks were prepared and dyed visible by using different food colourings. The mixing of the bio-inks was analyzed using the RGB values as a correlation. The parameters were measured using the Adobe Capture application. The effect of microfluidics on the reproducibility of printing was tested using different-sized printed objects. Moreover, the post-crosslinking method of alginate by spraying CaCl2 during the printing was compared to other crosslinking methods. The results of this project emphasize the importance of using microfluidics in 3D bioprinting in the future. Achieved RGB values indicate a good mixing of different coloured materials. The multifunctionality of fluidic chips enables many applications, such as material mixing and crosslinking during printing. One of the possible modifications of spraying could be creating an aseptic environment with specific conditions inside the printing hood during the bioprinting.
Keywords: 3D bioprinting, microfluidics, alginate, crosslinking, spraying